Computational Analysis of Horizontally and Inclined Finned Solar Air Collector - Halefom Kidane; Janos Buzas; Istvan Farkas (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2023)
ABSTRACT The majority of researchers have carried out simulations using computational fluid dynamics (CFD) and experimental investigation for design, manufacturing, performance evaluation, understanding flow behavior, efficiency prediction, condition optimization, etc. The main objective of the recent paper is to compare horizontally finned and 45° inclined finned solar air collector absorbers and to select the better construction using numerical simulation. ANSYS Fluent Workbench 2022 with renormalization-group (RNG) group k–ε turbulence model was applied for the analysis of the computational domain of solar air heaters. The simulation results generated using CFD were validated with data from the literature, and the simulation results were in agreement with experimental results from the relevant literature. Based on the simulation results the horizontal finned solar air collector absorber has better heat transfer behavior than the 45° inclined. ABSTRAK Mayoritas peneliti umumnya melakukan simulasi menggunakan perangkat komputasi, seperti computational fluid dynamic (CFD) dan eksperimental untuk menunjang keperluan desain, rancang bangun sistem, evaluasi kinerja dan karakteristik aliran, memperkirakan kinerja, serta optimalisasi, dll. Target dari makalah ini adalah membandingkan pemanas udara surya dengan sirip posisi horizontal dan miring 45° yang dipasang pada kolektor surya untuk memilih konstruksi terbaik secara numerik. ANSYS Fluent Workbench 2022 dengan model turbulensi k–ε renormalisasi grup (RNG) digunakan sebagai perangkat simulasi. Hasil simulasi divalidasi dengan data eksperimental dari literatur yang relevan, dan memperlihatkan kecenderungan yang sama. Berdasarkan simulasi, kolektor udara surya bersirip horizontal mempunyai karakteristik perpindahan panas yang lebih baik dibandingkan dengan kolektor udara bersirip miring 45°.